Perencanaan Mini Hidro Di Persawahan Pahae Jae Desa Nahornop Marsada Kabupaten Tapanuli Utara - Ronaldo Simatupang; Muhammad Fadlan Siregar (Riau Jurnal Teknik Informatika, 2025)
The design and construction of mini hydro in Pahae Jae rice fields, Nahornop Marsada village, North Tapanuli Regency, aims to utilize the potential of existing water resources to produce sustainable electrical energy. With supportive geographical conditions, the river flow in this area has sufficient discharge to be processed into electrical energy through a micro hydro power generation system. This study involves analyzing the potential of river flow, selecting strategic locations, and designing efficient turbine systems. The methods used include measuring water discharge, calculating the power that can be generated, and designing supporting infrastructure. The results of this design and construction are expected to provide alternative energy solutions for local communities, increase agricultural productivity, and reduce dependence on fossil fuel sources. In addition, this project also aims to increase public awareness of the importance of utilizing renewable energy and preserving the environment. Thus, the mini hydro in Pahae Jae not only functions as an energy source, but also as a model of sustainable development that can be applied in other areas with similar potential.